Brain abscesses in Iraq during a 10 years period: Part 11. Diagnostic investigations, management -and outcome. - Al-Tamimi, Zahra’a A.J.; Al-Hadithi, Tariq S.; Al-Khalili, Abdul- Hadi; Al-Diwan, Jawad K. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: This study comprises0two parts, the first one dealt with epidemiology, etiology and clinical picture of"brain abscess. This part describes diagnostic investigations, management and final outcome of brain abscess during a 10 years period. Methods: The case records of patients with brain abscess admitted to the neurosurgical specialties hospital in Baghdad over a 10 years period extending from 1 " Jan. 1993 to 3 1 " Dec. 2002, inclusive were reviewed. Data obtained included demographic and clinical data. Results: Results of peripheral leukocytes count, ESR and CSF were supportive in 16.7%, 67.9% 78` o ol’cases in which tests were applied, respectively. CT scan was suggestive in 100% of cases. Use of antibiotic therapy as a preliminary treatment line was adopted in 37.8% of cases, while surgery as a preliminary line of treatment was adopted in 62.3% of cases. Out of 68 cases, complete resolution was encountered in 70.6°x% ol’cases, sequlae in 11.8% and death in 17.9%. Bad neurological ’status on admission was the most encountered contributing factor for death. Metastasis from a remote infection process is a risky aetiology contributing to bad prognosis. Conclusion: The use Of C I Scan represents all important change in the diagnostic regimen of brain abscess in the last 10 -15 years.